Contribuições do design estratégico para o desenvolvimento de novos modelos de negócios no contexto de empresas startups - Almada, Viviane da Silva (Universidade do Vale do Rio dos Sinos, 2015)
Organizations, specifically startups, are situated in markets where the need to look into solving complex problems and the search for innovation are increasingly growing. In this context we highlight the strategic design as an approach that allows space expansion of the problem to be solved in the same way that increases the possibilities for innovation and brings project dimension of constant experimentation. This research aims to provide clues to analyse the contribution of the strategic design approach in the search for innovation, along with the use of the Business Model Canvas tool (BMC), within the reality of startups. The business environment of these companies was chosen considering organizations that drive innovation, embryonic and that have not yet reached the maturity of financial resources but with great economic importance in the job creation and technological innovation scene. Whereas Canvas, which aims to turn organizations more innovative and find new business formats allowing anyone to create or modify their business model was chosen because it is a user-friendly management tool and recognised in the current market organizations. Based on that, the research has a theoretical framework that supports the study, the environmental understanding to be searched and the implementation of the strategic design, through research-action, conducted at BoardShore startup, an e-commerce company that sells equipment for water sports, in Porto Alegre. Thus, we sought to examine the possibility of a deeper reflection about the possible contribution of strategic design, in conjunction with the implementation of the BMC as this tool aims to develop new business models. The results of this study show the importance of applying and adapting the design and management tools to a particular environment of the organization and the relevance of the strategic designer role in this design process.
Keywords: Design estratégico; Inovação; Canvas; Novos modelos de negócios; Startups; Strategic design; Inovation; New business models; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial